Development of an android-based numeracy literacy test using iSpring Suite in a Bengkulu coastal context - Elwan Stiadi; Ari Putra; M. Zainudin; Meidy Putra Areka; Ahbi Mahdianing Rum; Nader U-sin (Jurnal Elemen, 2026)
The Minimum Competency Assessment (MCA) is Indonesia’s national instrument for measuring foundational competencies, including numeracy literacy. However, findings from the Programme for International Student Assessment and the MCA indicate that many students still perform at low levels, partly because test items rely on limited, less contextualized problem settings. This study developed an Android-based numeracy literacy test using iSpring Suite by embedding items within the historical heritage context of the Bengkulu Coast to support students’ assessment preparation. The instrument was designed using the ADDIE model (analysis, design, development, implementation, and evaluation) and piloted with ninth-grade students in Bengkulu City, Indonesia. Data were collected through interviews, questionnaires, documentation, and item try-outs, and analyzed for content validity, reliability, practicality, item difficulty, and discrimination. The expert review confirmed the feasibility of the content, construct, and language. Empirical results for 10 items showed acceptable to strong validity, high reliability (0.781), difficulty levels ranging from easy to moderate, and discrimination indices from moderate to very good. The practicality score reached 84.7% (very practical), indicating that contextualized mobile-based assessment is a valid and practical alternative for numeracy learning.